Functional diversity and nutritional content in a deep-sea faunal assemblage through total lipid, lipid class, and fatty acid analyses - Parzanini, Camilla (PLoS One, 2018)
Lipids are key compounds in marine ecosystems being involved in organism growth, reproduction, and survival. Despite their biological significance and ease of measurement, the use of lipids in deep-sea studies is limited, as is our understanding of energy and nutrient flows in the deep ocean. Here, a comprehensive analysis of total lipid content, and lipid class and fatty acid composition, was used to explore functional diversity and nutritional content within a deep-sea faunal assemblage comprising 139 species from 8 phyla, including the Chordata, Arthropoda, and Cnidaria. A wide range of total lipid content and lipid class composition suggested a diversified set of energy allocation strategies across taxa. Overall, phospholipid was the dominant lipid class. While triacylglycerol was present in most taxa as the main form of energy storage, a few crustaceans, fish, jellyfishes, and corals had higher levels of wax esters/steryl esters instead. Type and amount of energy reserves may reflect dietary sources and environmental conditions for certain deep-sea taxa. Conversely, the composition of fatty acids was less diverse than that of lipid class composition, and large proportions of unsaturated fatty acids were detected, consistent with the growing literature on cold-water species. In addition, levels of unsaturation increased with depth, likely suggesting an adaptive strategy to maintain normal membrane structure and function in species found in deeper waters. Although proportions of n-3 fatty acids were high across all phyla, representatives of the Chordata and Arthropoda were the main reservoirs of these essential nutrients, thus suggesting health benefits to their consumers.